Criminal Responsibility for the Offense of Using Explosives Without Authorization in Fishery Practices (A Case Study of Court Decision No. 1220/Pid.Sus/2024/PN Tjk) - Hadahusi, Rafli Al; Rusli , Tami (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The criminal act of using explosives without authorization in fishing activities constitutes a form of crime that not only violates criminal law but also causes serious damage to marine ecosystems. This study aims to analyze the criminal liability of perpetrators in cases involving the use of explosives for fishing, as reflected in Court Decision No. 1220/Pid.Sus/2024/PN Tjk. The research method employed is normative juridical with a case study approach, examining relevant legislation and analyzing the judge's considerations in the ruling. The findings indicate that the defendant was legally and convincingly proven to have violated Article 1(1) of Emergency Law No. 12 of 1951 and Article 84(1) of Law No. 45 of 2009 concerning Fisheries. The judge imposed imprisonment and fines as a form of criminal liability for the act committed. This study emphasizes the importance of strict law enforcement against the use of explosives in fishing to protect the sustainability of marine resources and maintain public order. The research combines a normative juridical approach with an empirical approach. Data were collected through literature review, observation, interviews, and documentation.